An analysis of students' knowledge on PTPTN loan obligation: UiTM Pahang student's perspective / Mohd Samsuri Ghazali …[et al.] - Ghazali, Mohd Samsuri; Azwan, Mohd Faizal Azrol; Dali, Fadli; Ab Rashid, Elfee (2014)
Report from local newspaper shows PTPTN has disbursed RM 50.9 billion of money up to August 2013 for the purpose of student loan. Non-repayment of the loan among university students after they have graduated becomes a major problem to the government since the total amount of loan available to the students is depended on the loan repayment. The objective of this research is to know the level of knowledge among UiTM Jengka's student toward financial obligation/literacy on National Higher Education Fund (PTPTN). This research conducted by way of quantitative research method and the data were collected using questionnaire passed to 60 students of UiTM Jengka. The finding revealed that students lack of knowledge/literacy about certain aspect of PTPTN loan and it is highly recommended to the UiTM management to conduct a session explain about PTPTN loan information to students.